Tuberculosis in Older Adults: Seattle and King County, Washington. (12th April 2019) - Gardner Toren, Katelynne; Spitters, Christopher; Pecha, Monica; Bhattarai, Sanju; Horne, David J; Narita, Masahiro
Abstract: Background: In the United States, tuberculosis (TB) incidence rates are highest among adults aged ≥65 years. We performed this study to evaluate outcomes of older patients undergoing treatment for TB disease, including the frequency of adverse events related to TB treatment. Methods: This study evaluated adult patients who were diagnosed with pulmonary TB from 2009 to 2014 in King County, Washington. Patient characteristics, manifestation of TB, and treatment outcomes in different age groups were compared. Frequency and type of adverse events that resulted in treatment interruption were evaluated and patients aged ≥65 years were compared with selected younger patients. Results: There were 403 patients who met the study criteria, 111 of whom were aged ≥65 years. Older patients were significantly less likely to have cavitation on chest radiographs. Patients aged ≥65 years were less likely to complete TB treatment (76.6% vs 94.9%, P < .0001) and were more likely to die during treatment (18.9% vs 2.1%, P < .0001). The difference in these outcomes was heightened for those aged ≥75 years compared with those aged <75 years. Those aged ≥75 years were also more likely to have an adverse event attributable to TB medication and were more likely to have an adverse event later in therapy. Regardless of age, pyrazinamide was responsible for the majority of adverse reactions. Conclusions: Adults aged ≥65 years with pulmonary TB had less-advanced disease but a higher risk of complications during treatment such as death or adverse events. This effect was most pronounced among those aged ≥75 years. Abstract : Adults aged ≥65 years with pulmonary tuberculosis have less-advanced disease but a higher risk of complications during treatment such as death or adverse events. This effect was most pronounced among those aged ≥75 years.